2023
DOI: 10.48048/tis.2023.6528
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Compositions, Nutritional Contents, Cytotoxicity and Anti-Inflammatory Activity of Different Extracts from Spirogyra neglecta (Hassall) Kützing

Abstract: Spirogyra neglecta (Hassall) Kützing is an edible freshwater macroalga. It is available and consumed as local food in Thailand, especially in the northern and northeastern parts. To ascertain its good benefit for health and safe for consumption, this study was, therefore carried out to determine the phytochemical compositions, nutritional contents, cytotoxicity, and anti-inflammatory activity of the different extracts from S. neglecta. The extracts were prepared by using different solvents, such as propylene g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…S. neglecta alga was previously reported for its antioxidant, anti-bacterial and anti-inflammatory properties [ 22 , 23 , 36 , 37 ]. Regarding anti-cancer properties, S. neglecta water extract demonstrated in vivo cancer chemopreventive effects on DEN-induced hepatocarcinogenesis [ 25 ] as well as on the management of early stages of colon carcinogenesis in rat models [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…S. neglecta alga was previously reported for its antioxidant, anti-bacterial and anti-inflammatory properties [ 22 , 23 , 36 , 37 ]. Regarding anti-cancer properties, S. neglecta water extract demonstrated in vivo cancer chemopreventive effects on DEN-induced hepatocarcinogenesis [ 25 ] as well as on the management of early stages of colon carcinogenesis in rat models [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spirogyra sp. exhibits valuable curative properties, serving as a remedy for ovicidal, antifungal, antibacterial immunostimulant, and acaricidal activities (Ontawong et al 2013;Thumvijit et al 2014;Surayot et al 2015;Arjsri et al 2021;Yongkhamcha and Buddhakala, 2023). As Yosboonruang et al (2020) reported, isolating an antibacterial compound from S. neglecta has demonstrated activity against pathogens, including S. aureus, S. epidermidis, E. coli and Pseudomonas aeruginosa.…”
Section: Introductionmentioning
confidence: 97%